Biomechanical Evaluation of Hemiarthroplasty in the First Proximal Phalanx. A Finite Element Study - Madrid Pérez, Mario Alberto; Becerro de Bengoa Vallejo, Ricardo; Bayod López, Javier (Revista Mexicana de Ingenieria Biomedica, 2021)
Hallux rigidus produces a decrease in the dorsiflexion of the first metatarsophalangeal joint and is usually associated with the appearance of osteophytes. Hemiarthroplasty in the first proximal phalanx is a recommended surgical procedure in patients with advanced grade of hallux rigidus. Finite element analysis allows us to understand the biomechanical behavior of the foot. The objective of this work is to evaluate the biomechanical effects of an hemi implant placed in first proximal phalanx. Two models of finite elements are going to be compared, one free of pathologies and the other with a hemiarthroplasty in the first ray of the foot. We detected after inserting the prosthesis in the model that passive windlass mechanism is lost, and the lesser toes become overloaded, which leads to a loss of efficiency in gait as well as being able to cause postsurgical medical complications.